الوعي والممارسات المتعلقة بالرضاعة والفطام لدى األمهات في مدينة مصراتة :دراسة وصفية تحليلية (Comprehensive Journal of Science, 2025)
This descriptive-analytical study aimed to evaluate mothers’ awareness and practices relatedto breastfeeding and weaning in Misrata, Libya. A random sample of 210 mothers withchildren under the age of two was included. The results showed that a substantial proportionof mothers initiated breastfeeding within the first few hours after delivery (25.2%immediately after birth and 28.6% within the first hours). The majority practiced mixedfeeding (71.9%), with insufficient breast milk supply reported as the primary reason for usingformula. Regarding weaning, most mothers (56.7%) adopted a gradual approach, which isrecommended from both psychological and health perspectives to support the child’semotional and physical development. Statistical analysis revealed significant associationsbetween breastfeeding and weaning practices and several factors, including the child’s birthorder, mode of delivery, maternal age, educational level, and household income. Thesefindings emphasize the need to strengthen maternal health education programs to improvebreastfeeding and weaning practices, especially considering the heavy reliance on nonmedical sources of information. The study recommends implementing continuous awarenessinitiatives to enhance knowledge and promote healthier infant feeding behaviors, therebycontributing to improved child health and development outcomes
Keywords: Breastfeeding – Weaning – Maternal Awareness – Misrata City – Demographic Factors.